PELATIHAN PEMBUATAN ECO ENZYME DI KELURAHAN RUMBAI BUKIT, PEKANBARU - Listihana, Wita Dwika; Lubis, Nurhayani; Onasis, Dini (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2024)
This service was carried out in the Rumbai Bukit Village. It will be held on September 30, 2022. This service is a follow-up to the MOA of the Faculty of Economics, Unilak, with the Rumbai Bukit Village in implementing the Tri Dharma of higher education. The choice of training on processing organic waste into eco enzyme was due to the fact that villagers in Rumbai Bukit Village had not received education about waste management. So this is considered important, because if viewed globally, waste is an issue that is still being discussed in recent times. Households are the biggest contributor to waste generation in densely populated areas such as Pekanbaru. So, one of the solutions to reduce waste generation is to process waste from home. One way is to turn waste into eco enzymes. The service was carried out on September 30 2022, with the service partners being PKK members of the Rumbai Bukit Village. Followed by 29 participants, this activity went very well. The transfer of knowledge on making eco enzyme was carried out very well. This can be seen from the results of the questionnaires distributed before and after the training. Prior to the training, most of the participants did not know what eco enzyme was, both how to make it and the benefits of eco enzyme. After the dedication, almost all participants understood and understood how to make eco enzymes and the benefits of these eco enzyme. Keywords: Eco enzyme, household waste, organic waste